Ultrasound parameters of normal lacrimal sac and chronic dacryocystitis - Machado,Marco Antonio de Campos (2017)
ABSTRACT Purpose: To compared the ultrasound findings of the lacrimal sac between subjects with normal lacrimal systems those with chronic dacryocystitis. Methods: A retrospective study of 10 subjects with a normal lacrimal system (Group 1) and 10 with chronic dacryocystitis (Group 2) diagnosed according to B-mode ultrasound with a 10-MHz transducer and the direct-contact technique (AVISO, Quantel Medical) for lacrimal sac assessment. We analyzed the dimensions, features, and content of the sacs. Characteristics of the population: female: 6, Group 1; 8, Group 2; mean age 48.4 years (SD=19.9; range, 22-80 years), Group 1; 50.5 years (SD=15.5; range, 25-75 years), Group 2. Results: The dimensions of the lacrimal sac were as follows: anteroposterior 1.86 and 10.99 mm in Groups 1 and 2, respectively, p<0.0001; vertical 9.79 and 14.13 mm in Groups 1 and 2, respectively, p=0.049. Qualitative evaluation of the lacrimal sac contents showed hypoechogenic content in Group 1 (10, 100%) and hyperechogenic punctiform content in Group 2 (10, 100%) with partial filling in seven cases (70%). Conclusions: Ultrasonography can differentiate normal lacrimal sacs from sacs compromised by chronic dacryocystitis, thus being useful as an adjunct to clinical examination and surgical planning.